Giinaquq Like a Face : Suqpiaq Masks of the Kodiak Archipelago - Steffian, Amy F.; Haakanson, Sven D. (Book collections on Project MUSE., 2009)
Masks are an ancient tradition of the Alutiiq people on the southern coast of Alaska. Alutiiq artists carved the masks from wood or bark into images of ancestors, animal spirits, and other mythological forces; these extraordinary creations have been an essential tool for communicating with the spirit world and have played an important role in dances and hunting festivities for centuries. Giinaquq: Like a Face presents thirty-three full-color images of these fantastic and eye-catching masks, which have been preserved for more than a century as part of the Pinart Collection in a small French museum. These masks, collected in 1871 by a young French scholar of indigenous cultures, are presented for the first time in their complete cultural context, celebrating the rich history of the Alutiiq people and their artistic traditions.